Quality evaluation of lassi sold in Kolhapur city - Munde, BB; Patange, DD; Shendurse, Ashish Maruti; Kamble, DK; Sawale, Pravin Digambar (Indian Journal of Dairy Science, 2017)
Lassi of various brands are been prepared and marketed in Kolhapur city of Maharashtra. On the basis of preliminary survey, the most popular six brands of lassi were selected and coded with KS1, KS2, KS3, KS4, KS5 and KS6 which were brought to the laboratory under chilled condition. The sensory, physico-chemical and microbial qualities of lassi were studied. Colour and appearance, body and texture, flavour, consistency and overall acceptability were significantly (P<0.05) affected by the brands of lassi sold in Kolhapur city. Lassi of KS1 brand recorded maximum overall acceptability score (8.29) followed by KS4 (8.09), KS6 (8.06), KS2 (7.73), KS5 (7.56) and KS3 (7.42). There were significant variation in respect of fat, protein, sucrose, total sugar and total solids content in all the lassi samples. Along with the quite good number of lactic acid bacteria count in lassi, the occurrence of coliform and yeast and mould count were recorded in all samples. The SPC (x107 cfu/ml) recorded in KS1, KS2, KS3, KS4, KS5 and KS6 of market lassi samples were 13.17, 10.36, 7.65, 8.50, 11.81, and 6.75, respectively and the difference in count were significant whereas, the average LAB content of lassi varied from 3.89 to 7.90 (x105 cfu/ml). It can be concluded that the wide variation was found among the market lassi samples, due to lack of awareness to maintain hygienic and nutrition condition and unavailability of suitable techniques in manufacturing of lassi.